Religion Simulacrum in Open World Video Game - Wilujeng, Panggio Restu; Wijayanti, Nurvita (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
Apart from being a medium for entertainment simulation, video games also provide a representation of the social world. Game industry developers always carry out research to provide socio-cultural, historical and philosophical system content to enrich the content in the game. The story background in video games aims to provide experiences and impressions for the players. This research aims to qualitatively explore forms of religious representation that are simulated in open world video games. So players can play role characters in the game to experience spirituality and religiosity. Either through latent and manifest narratives or through moral choices in the context of developing the storyline and Player character in the Game. This research uses Emile Durkehim's sociological perspective of religion regarding Karl Marx's totemism and commodity fetishism to observe the incarnation of the gaming industry as an altar of worship for its players, as well as Jean Baudrillard's postmodernist perspective with his simulacrum concept to analyze the form of simulation and representation of religious symbols that appear in the game. these open world games... This research finds that the use of simulations and the distribution of representations of religious signs or symbols in games forms a religion simulacrum or a blurring of spiritual boundaries between the pseudo and the real. Video games build the Player's construction of religiosity and spirituality virtually in a simulated world that contains ritual practices, ethics, morality, cosmology, metaphysics, and theology.